Penerapan Arsitektur Perilaku Dalam Perancangan Kampung Vertikal Di Kota Makassar - A. Tenri Rawe, Andi Nurjannah; Said, Ratriana; Alfiah, Alfiah (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2023)
Population density is an essential issue for a country, especially Indonesia, because of its enormous impact on its progress. Demographically and in terms of development aspects, Makassar City is one of the largest cities in Indonesia, with various ethnic groups living. As a service center in the eastern region of Indonesia, Makassar City plays a role in trade and service centers, industrial activities, government activities, freight and passenger transportation service nodes, land, sea, and air, and education and health service centers. This then causes the population growth rate in Makassar City to become uncontrollable and, of course, causes problems in the housing sector. The negative physical aspects that arise require a strategy to solve them. To overcome this, vertical villages can be used to reduce slum settlements and for the need for land for housing in urban areas, especially Makassar City. The design of vertical villages uses a behavioral architectural approach because this approach can respond to human needs and feelings that adapt to the human lifestyle in it. In reality, an architect’s imagination in the design process will produce different results after the process of use or occupancy. For this reason, it is necessary to understand basic human needs and how architectural design relates to human and environmental behavior. The selection of the design location was also based on various criteria or considerations, including being in the city center, an area with a high population density, and an integrated residential area.